Вы находитесь на странице: 1из 2

Homework 7

Problem 1
a) TRUE.

This states that for every x, there is a y greater than x. Since the natural numbers do not
have an upper bound, there will always be a number larger than any other number, so
this is TRUE.


This states that for any number x, there is a value y that is less than x. The natural
numbers are bounded below, and if x = 0, then there is no y in N that is less than x, so
this statement is FALSE.

c) TRUE.

This states that there is a number y for every number x that is either less than or equal
to x. Because there is always a number y that is equal to x (they can just be the same
number!) this statement is TRUE.

d) TRUE. This states that for every x and y, there are numbers z and w such that x+y = z or
x+y = w. Because every sum of natural numbers x and y is itself a natural number, it is
equal so some number w and z (where w and z are both set to the value of the sum of x
and y).

e) TRUE. By the transitive property, if (x+y) = z and w = (x+y), then w=z. Thus, there can be
no value z and w where they are both equal to (x+y) but not equal to each other. (The
problem asked for an explanation, but a rigorous proof can be constructed by

f) TRUE. This states that there exists an x and y such that x is less than y, and for any value
z, if z is also less than y, then it implies that x = z. All we need to do to show that it is true
is to find one pair of x,y values where it is the case for all z < y.

Take y = 1, x = 0. We have that x < y.

The only z < y is 0. Thus, for all z less than y, x = z.
Since both of these statements are true, the AND is true.

Problem 2
a) ∃x(2 * x = 12)

b) ∀a∀b(¬(a*b = 12) ∨ ((a = 1) ∨ (b = 1)))

c) ∀x ∃y((2 * y = x) ∨ ((2 * y = x + 1))

Problem 3
This will be done in parts:

a) Let prime(x) be that x is prime: ∀a∀b(¬(a*b = x) ∨ ((a = 1) ∨ (b = 1)))

b) Let even(x) be that x is even: ∃y(2 * y = x)

Our final result is: For a number x, either it is not even or it is the sum of two primes (in
other words, if x is even -> it is the sum of two primes)

∀x(¬even(x) ∨ ∃a∃b(prime(a) ∧ prime(b) ∧ a+b = x))